2013
DOI: 10.1590/s0034-72802013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Perfil refracional dos présbitas na Amazônia brasileira

Abstract: Resultados: Dos pacientes atendidos, 53,0% eram do sexo feminino; a faixa etária mais prevalente era de 51 a 60 anos; 66,0% não são aposentados e ainda desenvolvem alguma atividade laborativa; a maior prevalência das ametropias registrada foi de astigmatismos diversos (43,0%) e a acuidade visual para longe, sem correção, foi de 15,0% com 20/200 e, com correção, foi de 45,0% com 20/30 ou mais; em relação à visão para perto, a acuidade visual foi de 40,0% para J6, sem correção e, de 82,0% para J2 e J1, com corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…This confirms our findings. Indeed, since the amplitude of accommodation is greater in myopes than in hypermetropes, presbyopia would manifest itself later in myopes, according to Mc Brien, et al, after a study of the amplitude of accommodation in students aged 18 to 22 [11]. On the other hand, Schaeffel, et al, have shown that refractive disorders do not influence the dynamics of natural accommodation [12].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms our findings. Indeed, since the amplitude of accommodation is greater in myopes than in hypermetropes, presbyopia would manifest itself later in myopes, according to Mc Brien, et al, after a study of the amplitude of accommodation in students aged 18 to 22 [11]. On the other hand, Schaeffel, et al, have shown that refractive disorders do not influence the dynamics of natural accommodation [12].…”
Section: Discussionmentioning
confidence: 99%